EON – Business development challenges and opportunities - Bohlouli Ghashghaee, Bijan; Dhawan, Rohit; Misra, Anandita (2013)
E.ON is one of UK’s largest power and gas companies. E.ON’s new initiative known as ‘Target Operating Model’, which is believed to enhance customer experience and deliver operational benefits, is currently underway. The initiative includes enhancements in various areas such as training, processes, systems and website development. E.ON has a top-down approach in adopting the KPIs for these initiatives, starting from defining strategic objectives and cascading them to business function level.